The great plunder : how China lost its treasures in the 19th and 20th centuries - Chang, Qing, 1965-; Huang, Shan (Royal Collins Publishing Group, 2025)
"This book provides a comprehensive overview of the dispersal of Chinese cultural relics from the late 19th to the early 20th century. Following the Opium Wars, there was a surge of Western interest in uncovering treasures in China, leading to the removal of countless artifacts by foreign explorers and antique dealers. These national treasures were lost overseas, making their return to China nearly impossible. Beginning with the exploits of China's Western explorers, such as Sven Hedin, the book unfolds in eleven chapters, detailing the adventures of figures like Stein, von Le Coq, Otani Kozui, and others in locations such as Lop Nur, Dunhuang, and the Blackwater City. It chronicles their plundering of precious cultural relics, including the Berzic Caves wall paintings, Han Dynasty documents, Dunhuang documents, and numerous other valuable artifacts. Filled with meticulously researched historical details, this book serves as both a lament and a commemoration of a century of Chinese cultural relics dispersed worldwide." -- Amazon.com.